Edukasi Bahaya Penyebaran Berita Hoaks di Media Sosial pada Siswa SMA Negeri 1 Bubon - Iqwal Maulana Zikri; T.Fahri Dinata Arya; Muhammad Thaibatul Fata; T. Saiful Rahmat Tarsa; Arisman Arisman; Rahma Hidayanti; Elni Selvia; Rahmad Baihaqi; Iwan Doa Sempena (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This community service activity was conducted to enhance high school students’ understanding and awareness of the dangers of hoax news on social media. The socialization program was carried out at SMA Negeri 1 Bubon on May 9, 2026, involving 25 students as participants. The methods implemented included lectures, interactive discussions, question-and-answer sessions, and case study analysis. The results demonstrated that participants gained a better understanding of the concept, characteristics, and negative impacts of hoax news, as well as increased awareness of the importance of digital literacy in evaluating and filtering information on social media. Through this activity, participants were encouraged to become more critical and responsible in using digital platforms. Overall, the program is expected to contribute positively to efforts aimed at preventing the spread of hoax news within the school environment and the broader community. This school-based program was designed as a preventive effort in strengthening students’ digital literacy skills in order to reduce the risk of misinformation exposure.